The Effects of the Intrinsic Motivation and Extrinsic Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Alwi Assegaf Palembang - Muhammad Yusuf (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2021)
This study aimed to examine and analyze the effects of intrinsic motivation and extrinsic motivation on the performance of employees with job satisfaction as an intervening variable at PT. Alwi Assegaf Palembang. The number of respondents was 51 people. The data were collected using a questionnaire method with a Likert scale. They were examined and analyzed using the Smart-partial least square. Furthermore, the intrinsic motivation variable showed a significant positive influence on employee performance, but the extrinsic motivation variable did not have a significant influence on the performance of the employees. Job satisfaction was not an intervening influence between intrinsic motivation and employee performance and between extrinsic motivation and employee performance. The results showed that intrinsic motivation and extrinsic motivation had a significant positive effect on employee job satisfaction. The effect of the intrinsic motivation on the performance was significantly positive, while the extrinsic motivation was not significantly positive on the performance. In this study, job satisfaction was not an intervening variable between the intrinsic and extrinsic motivations on the performance. Abstrak Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh motivasi intrinsik dan motivasi ekstrinsik terhadap kinerja karyawan dengan kepuasan kerja sebagai variable intervening pada PT. Alwi Assegaf Palembang. Responden dalam penelitian ini berjumlah 51 orang. Data dalam penelitian ini diperoleh dengan menyebarkan kuisioner berupa pertanyaan dengan menggunakan skala Likert. Data dianalisis dengan smart-partial least square. Hasil penelitian menunjukkan bahwa motivasi intrinsic dan motivasi ekstrinsik berpengaruh positif signifikan terhadap kepuasan kerja karyawan. Pengaruh motivasi intrinsik terhadap kinerja adalah positif signifikan, sedangkan motivasi ekstrinsik menunjukkan tidak ada pengaruh signifikan positif terhadap kinerja. Kepuasan kerja bukan merupakan variabel intervening antara motivasi intrinsik dan ekstrinsik terhadap kinerja dalam penelitian ini. Kata kunci: Motivasi Intrinsik, Motivasi Ekstrinsik, Kepuasan Kerja, Kinerja